A model for the fragmentation kinetics of crumpled thin sheets - Jovana Andrejevic (Nature Portfolio, 2021)
The process of thin sheet crumpling is characterized by high complexity due to an infinite number of possible configurations. Andrejevic et al. show that ordered behavior can emerge in crumpled sheets, and uncover the correspondence between crumpling and fragmentation processes.